The Development of Worksheets Students Based I-Sets (Islamic, Science, Enviroment, Technology, Society) Skills to Train Students Think Critically - Laila Puspita; Ruhban Masykur; Yayan Eko Saputro; Komarudin Komarudin (Magister Pendidikan Biologi, Universitas Negeri Medan, 2022)
Skill think critically students should high to encourage students because of eliciting an ideas or thought about the problems education world new stuff. Skill and in fact think critically is still low, students this is device used not education can help in improving think critically students ability skill.The research of matter managed a study worksheets students development based i-sets to train students skill think critically high school biology class x-rays on learning.The kind of research used is research and development (R&D) referring to borg and gall .The 7 stages of used is Research and Information collecting, Planning, Develop preliminary form of product, Preliminary field testing , Main product revision , Main field testing , and Operational product revision , the research was done in sman 1 sungkai north class X mia 2. The result of studies do show (1) media experts assessment of 84,37 % with the criteria is very worthy, (2) judgment linguist by 87,49 % with the criteria is very worthy, (3) the assessment of the matter as much as 80,28 % with the criteria is very worthy. (4) response educator biology expressed very worthy of the percentage of 89,90 %.(5) response students class x mia 2 on the criteria is perfectly feasible with the percentage of 92,22 %.So that the teaching material worksheets students based i-sets fit for use as the teaching material in the process of learning biology.